All Eyes on Us: A Comparative Critique of the North Carolina Innocence Inquiry Commission - Dreger, Elena (2007)
Tourism as one of the biggest industries in the world has been changing continuously and rapidly. The publishing of the Brundtland Report in 1987 has accelerated the discussion about combining economic, social and environmental factors – the so-called triple-bottom line – in order to secure long-term sustainable living conditions on a finite planet for both business and society. This has lead to occurring pressure from different stakeholder groups as for example policy makers or non-governmental organizations (NGO’s) urging for more sustainable business practise within the industry whereas one important pressure group appears to be missing out in this context: the customers of mass tourism products and therefore the demand side within the economic equation. Tourists have been observed to be overall reluctant to pay price premiums for more sustainable travel alternatives and seem to “take vacation” from their everyday green behaviour. Hence at the current point of time eco-tourism appears to be a market niche in which mainly small-scale providers and NGO’s like Nature’s Best in Sweden operate. However integrating mass tourism into the consideration can be seen as a promising opportunity and from an environmental standpoint an urgent necessity as it can be argued that within an industry of this scale, even small improvements towards more sustainable behaviour bear the potential for a substantial impact. The purpose of this study therefore lies in researching the two marketing tools of brands and eco-labels and the influence they can have individually and in combination on the tourist’s decision making delimitated to the context of charter tourism in Sweden. Through the research of this study it was found that currently no directly applicable theory about the combination of brands and eco-labels seems to exist for marketing neither in general, nor for the tourism industry in particular. This strongly indicates the novelty of the topic of combining brands and eco-labels and points out research opportunities. In order to achieve this purpose, a mixed-method research design was used combining qualitative expert interviews from direct business representatives and a quantitative data collection utilizing the scholarly acknowledged marketing research method of conjoint analysis in one of its most up-to-date forms of an adaptive choice-based conjoint analysis. Theory from different fields of study as consumer behaviour and decision making, branding and eco-labelling as well as sustainability marketing was combined and translated into the new and emerging service category of sustainable tourism. From this a conceptual framework was developed combining the data collection results from the mixed-method approach. This leads to the identification of ways for improving current charter tourism companies’ marketing based on the customers’ current view on utilities within certain aspects of the tourism package. Overall this study therefore contributes to the discussion on how demand for sustainable products evolves and can likely be increased. This is seen as a valuable theoretical, practical and societal contribution as it helps improving tourism companies’ understanding of their customer base and supports offering products/services with an improved perceived individual and societal value for charter tourism companies that aim for a higher degree of sustainability in their objectives